“Spray, Spray, Spray!”: Insecticides and the Making of Applied Entomology in Canada, 1871-1914 - Cook, George (Scientia Canadensis, 1998)
ABSTRACTAs insecticides were adopted by Canadian farmers and fruit-growers after 1871, the resources conferred on economic entomology by the Dominion and Ontario governments grew. In 1886, with the establishment of the Experimental Farms system, James Fletcher, the Dominion entomologist and botanist, and his colleagues inherited the task of promoting insecticides to orchard-ists and others. In 1898-1900, in response to the arrival in Ontario of the San José scale, Canada and Ontario adopted laws mandating the use of insecticides, as sprays and fumigants, in orchards and at plant quarantine stations. To meet the resulting demand for trained technicians and scientifically-minded farmers, the institutions of applied entomology federally and at the Ontario Agricultural College were further developed. In 1910, after a decade of rapid diffusion of insecticides, Parliament adopted the Destructive Insects and Pest Act, thus creating a national system of horticultural hygiene.